Bovine brucellosis, associated risk factors and preventive measures in industrial cattle farms - Shahrokh Izadi; Vahid Moghaddas; Awat Feizi; Akram Bahreinipour; Zahra Barati (Heliyon)
Effective management of brucellosis in human populations is closely tied to controlling the disease in domestic livestock. This study focused on identifying determinants of brucellosis prevalence in mixed industrial dairy and beef cattle farms within Isfahan Province, Iran. Employing a case control design, we compared 32 ranches with documented brucellosis within the previous year (12 months) to 38 farms with no brucellosis during the same timeframe. The comparison examined the farms' adherence to health protocols for raising cattle. Utilizing multivariable logistic regression, the study identified several significant risk factors linked to brucellosis prevalence. These included cleaning milking accessories with a water and chlorine solution (OR 0.25, 95%CI 0.06 to 0.99), cleaning water troughs daily (OR 0.20, 95%CI 0.04 to 0.89), the cows' density per square meter (OR 0.14, 95%CI 0.03 to 0.75), being within 2000 m of another cattle ranch with brucellosis (OR 4.02, 95%CI 1.09 to 14.84) and ovine farms situated within a 500-m radius (OR 8.43, 95%CI 1.66 to 42.70). No meaningful difference was observed in vaccination frequency between infected and non-infected farms (P = 0.645). While vaccination is essential for preventing bovine brucellosis, robust biosecurity measures are crucial for effective disease management.